The justice of humans : subject, society and sexual violence in international criminal justice - Campbell, Kirsten, 1969- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2023)
Justice for conflict-related sexual violence remains a critical problem for global society today. This ground-breaking book addresses pressing questions for 'international justice': what do existing approaches to international justice offer to victims of war and societies in conflict? And what possibilities do they provide for feminist social transformation? The Justice of Humans develops a new feminist approach to 'international justice'. Adopting a socio-legal perspective, it studies two major contemporary examples of legal and feminist approaches to justice, the International Criminal Tribunal for the former Yugoslavia and the Women's Court (former Yugoslavia), focusing on their treatment of sexual violence as a gender-based crime. Drawing on feminist social theory, legal analysis, and empirical research, the book offers an innovative feminist framework for understanding 'international justice' and offers new theoretical and practical strategies for building feminist justice.
'The justice of humans?' outline of a feminist social theory of international criminal justice -- The international crime -- The international legal subject -- The international criminal trial -- International criminal justice -- The global legal form of international criminal law -- The women's court and the feminist approach to justice -- Building a feminist approach to justice for international criminal law : political challenges and conceptual foundations -- Building a feminist justice approach to international criminal law in practice : strategies for change.
Title from publisher's bibliographic system (viewed on 12 Dec 2022).
Keywords: International criminal law -- Social aspects; Rape as a weapon of war; Feminist jurisprudence; Rape as a weapon of war -- Former Yugoslav republics